English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Prove that if a^x = b^y = (ab)^xy, then x + y = 1

2007-04-18 13:04:51 · 4 answers · asked by Anonymous in Science & Mathematics Mathematics

4 answers

a^x = (ab)^(xy)
lg(a^x) = lg((ab)^(xy))
x.lg(a)=xy.lg(ab)
y=lg(a)/lg(ab)
b^y = (ab)^(xy)
lg(b^y) = lg((ab)^(xy))
y.lg(b) = xy.lg(ab)
x = lg(b)/lg(ab)
x+y = lg(b)/lg(ab)+lg(a)/lg(ab)
x+y = [lg(b)+lg(a)]/lg(ab)
but: lg(a.b) = lg(a) + lg(b)
x+y = (lg(a) + lg(b))/(lg(a) + lg(b))=1

2007-04-18 13:20:43 · answer #1 · answered by Anonymous · 0 0

The gist of the communicate available (sorry, there are too many pages to grant all the hyperlinks) is that wands help to concentration the magic resident interior the witch or wizard, yet wandless magic remains achievable, particularly for terribly gifted human beings like Snape and Dumbledore. some examples ... Apparition Assuming one's Animagus sort (or Metamorphpagus) Accio (the Summoning attraction) Elves can do magic without utilising wands Lumos

2016-12-10 05:46:11 · answer #2 · answered by klohs 4 · 0 0

xloga =ylogb = xy log ab = xy loga + xylogb
loga/y = logb/x = log ab
x = logb/logab
y = loga/logab
x+y = (logb +loga)/logab=logab/logab = 1

2007-04-18 18:07:57 · answer #3 · answered by ironduke8159 7 · 0 0

a^x = (ab)^xy
ln[a^x] = ln[(ab)^xy]
x ln[a] = xy{ln[a] + ln[b]}
y = ln[a]/{ln[a] + ln[b]}

b^y = (ab)^xy
ln[b^y] = ln[(ab)^xy] = xy{ln[a] + ln[b]} = y ln[b]
x = ln[b]/{ln[a] + ln[b]}

x+y = {ln[a]+ln[b]}/{ln[a]+ln[b]} = 1
because they have a common denominator

2007-04-18 13:18:12 · answer #4 · answered by kellenraid 6 · 0 0

fedest.com, questions and answers